Mesenteric ischaemia. Issue 7 (July 2022) - Nicholls, Jonathan; Brooks, Marcus
Abstract: Acute mesenteric ischaemic (AMI) is a life-threatening vascular condition from which outcomes are poor. It results from acute thrombosis or embolization of one or more mesenteric arteries. Chronic mesenteric ischaemia (CMI) is a clinical syndrome of abdominal pain after eating related to stenosis or occlusion of one or more mesenteric vessels associated with other cardiovascular disease. Mesenteric ischaemia can also result from hypoperfusion, non-occlusive mesenteric ischaemia (NOMI), or mesenteric vein thrombosis (MVT). This article looks at the epidemiology, diagnosis, and management of mesenteric ischaemia. It recognizes the need for resuscitation and time-critical resection of non-viable bowel and revascularization in the acute setting. Improving outcomes necessitates a multidisciplinary approach involving emergency medicine, diagnostic radiology, general surgery, vascular surgery, interventional radiology, anaesthetic, and critical care specialists.